2002
DOI: 10.1067/mva.2002.124627
|View full text |Cite
|
Sign up to set email alerts
|

Clinical failures of endovascular abdominal aortic aneurysm repair: Incidence, causes, and management

Abstract: In our 7-year experience, one or more clinical failures of endovascular AAA repair were observed in 31 patients (8.3%). Reinterventions were necessitated in a total of 10.7% of patients but were usually successful in maintaining AAA exclusion and limiting AAA growth. These results emphasize that endovascular repair provides good results and many benefits for most properly selected patients but is not as durable as standard open repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
84
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(91 citation statements)
references
References 48 publications
(54 reference statements)
5
84
0
2
Order By: Relevance
“…Most elective re-interventions are due to endoleak. The majority of acute re-interventions are required due to stentgraft thrombosis with acute limb ischaemia 7,9,11,[14][15] . Our experience with EVAR complications requiring intervention is comparable with other presented reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most elective re-interventions are due to endoleak. The majority of acute re-interventions are required due to stentgraft thrombosis with acute limb ischaemia 7,9,11,[14][15] . Our experience with EVAR complications requiring intervention is comparable with other presented reports.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular correction or conversion is determined to be the method of choice for most EVAR complications repair 7,9,[11][12][13][14][15] . The concept of having a "tool-box" con- .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research on the introduction of hemocompatibility to the surface of the stent-grafts has been actively carried out for the lifelong use of the stentgrafts [1,2], while endothelialization of the stent-grafts, another significant durability factor for the stent-grafts as was presented in Fig. 1, has not been much explored to prevent the fatal endoleak [3].…”
Section: Introductionmentioning
confidence: 99%
“…Effectiveness of EVAR in the long-term has to be proven and studies are underway ; some doubts remain if the procedure is indicated in young patients and in low-risk patients (18).…”
mentioning
confidence: 99%